Management of Energy Production in a Hybrid Combination of a Heat Pump and a Photovoltaic Thermal (PVT) Collector - Wojciech Luboń; Artur Jachimowski; Michał Łyczba; Grzegorz Pełka; Mateusz Wygoda; Dominika Dawiec; Roger Książek; Wojciech Sorociak; Klaudia Krawiec (Energies)
The purpose of the study is to investigate the energy performance of a PVT collector in combination with a heat pump. First, a test system combining a heat pump and PVT module is built, and then its performance is carefully measured, assessing the electricity and heat production. The paper focuses on increasing the efficiency of a photovoltaic (PV) panel (as part of the PVT module) by cooling it with a heat pump. The main idea is to use the heat generated by the warming panels as a low-temperature source for the heat pump. The research aims to maximize the use of solar energy in the form of both electricity and heat. In traditional PV systems, the panel temperature rise reduces the solar-to-electric conversion efficiency. Therefore, cooling with a heat pump is increasingly used to keep panels at optimal temperatures and improve performance. The tests confirm that cooling the panels with a heat pump results in an 11.4% improvement in electrical efficiency, an increase from 10.8% to 12.0%, with an average system efficiency of 11.81% and a temperature coefficient of –0.37%/°C. The heat pump achieves a COP of 3.45, while thermal energy from the PVT panel accounts for up to 60% of the heat input when the air exchanger is off. The surface temperature of the PVT panels varies from 11 °C to 70 °C, and cooling enables an increase in electricity yield of up to 20% during sunny periods. This solution is especially promising for facilities with year-round thermal demand (e.g., swimming pools, laundromats).